The Effect of Motivation and Work Environment on Employee Performance at PT. Gapura Angkasa at Lombok International Airport - Dhita Nilma Rizkillah; Septiyani Putri Astutik (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Advances in technology and information development affect a performance achievement. Employee performance can be influenced by motivation. In addition to motivation, employee performance is also influenced by the work environment. One of the main problems in human resources is how to improve the performance of employees. This study used a quantitative method by distributing questionnaires. The questionnaire in this study was distributed to 46 respondents. This study used data analysis techniques, namely instrument testing, classical assumption testing, regression analysis and hypothesis testing. The results of this study are that there is a joint influence between motivation and work environment on the performance of employees of PT. Gapura Angkasa at Lombok International Airport. This is reinforced by the results of the calculation of the coefficient of determination where R is 0.768 with R2 of 58.9%.